Regulating T Cell Population Alleviates SLE by Inhibiting mTORC1/C2 in MRL/lpr Mice - Zhang, Dongya; Wang, Meiling; Shi, Guoping; Pan, Peng; Ji, Jianjian; Li, Pengfei (Frontiers in Pharmacology, 2021)
Patients with systemic lupus erythematosus (SLE) have T-cell dysfunction that has been attributed to the activation of the mammalian target of rapamycin (mTOR). Rapamycin inhibits antigen-induced T-cell proliferation via mTORC1 and has been developed as a medication for improves SLE primarily. Our previous studies showed that INK128, a selective, highly potent, and orally inhibitor of mTORC1 and mTORC2 also significantly attenuates SLE in pristine-induced lupus mice. In this study, we aimed to compare the cure effects of INK128 and rapamycin on SLE. MRL/lpr mice were treated with INK128 and rapamycin beginning at 12 weeks of age. The impact of T cell populations was investigated using flow cytometry. MTOR signaling was measured by Western Blot. INK128 remarkably alleviated SLE by reducing splenomegaly, renal inflammation and damage, and resuming T-cell dysfunction. INK128 has more effective on improving SLE than rapamycin. INK128 effectively suppressed mTORC1 and mTORC2 activity in T cell. However, rapamycin just suppressed mTORC1 activity. Furthermore, in vitro experiments confirmed that INK128 had more effectively effects on T cell dysfunction than rapamycin. Collectively, our results suggest INK128 may be a potential therapeutic candidate for the treatment of SLE.